I'm looking for a method to evaluate the following integral:

$\displaystyle \int_0^{\infty} \left( \frac{1}{e^x - 1} - \frac{1}{x} + \frac{e^{-x}}{2} \right) \frac{1}{x} dx$


Using the link, here's what I've done so far. Define

$F(s) = \displaystyle \int_0^{\infty} e^{-sx} \left (\frac{1}{e^x - 1} - \frac{1}{x} + \frac{e^{-x}}{2} \right) \frac{1}{x} dx$.

Supposing we've shown that this integral converges nicely enough to justify differentiating underneath it, we have that

$F'(s) = \displaystyle -\int_0^{\infty} e^{-sx} \left(\frac{1}{e^x - 1} - \frac{1}{x} + \frac{e^{-x}}{2} \right) dx = - \left( \int_0^{\infty}e^{-sx} \frac{e^{-x}}{2} dx + \int_0^{\infty} e^{-sx} \left( -\frac{1}{x} + \frac{1}{e^x - 1} \right) dx \right)$.

We recognize that the first integral is the Laplace transform of $\frac{e^{-x}}{2}$ and so the integral evaluates to $\frac{1}{2(s+1)}$.

Setting $F_2(s) \displaystyle \int_0^{\infty} e^{-sx} \left(-\frac{1}{x} + \frac{1}{e^{x} - 1} \right) dx$, (and assuming a similar analysis will justify the differentiation), we find that

$F'_2(s) = \displaystyle \int_0^{\infty} e^{-sx} - \frac{x e^{-sx}}{e^x - 1} dx = \frac{1}{s} - \int_0^{\infty} \frac{xe^{-sx}}{e^x - 1} dx $.

While I'm pretty sure I can justify the convergence of all the relevant integrals to differentiate, this last integral is not the Laplace transform of a function I'm familiar with (which doesn't mean much, because I'm not familiar with many). Any tips on how to take care of the last integral?

  • $\begingroup$ Do you mean that the expression in divided by x or $d(\frac xx)$ $\endgroup$ – superAnnoyingUser Mar 3 '13 at 19:40
  • $\begingroup$ The entire expression is divided by x. I've changed the notation to reduce ambiguity. $\endgroup$ – anonymous Mar 3 '13 at 19:42
  • $\begingroup$ Ah. I did not see that at all, deleted my first response. $\endgroup$ – muzzlator Mar 3 '13 at 19:43
  • 2
    $\begingroup$ A related problem. $\endgroup$ – Mhenni Benghorbal Mar 3 '13 at 19:48

$$f(\lambda)=\int_0^{\infty} \frac{e^{-\lambda x}}{x}\left(\frac{1}{e^x-1}+\frac{1}{2e^x}-\frac{1}{x}\right)dx$$

$$\begin{align*}f''(\lambda)&=\int_0^{\infty} e^{-\lambda x}\left(\frac{x}{e^x-1}+\frac{x}{2e^x}-1 \right)dx\\&=\int_0^{\infty} \frac{x}{e^{\lambda x}(e^x-1)}dx+\int_0^{\infty}\frac{x}{2e^{(\lambda +1)x}}dx-\int_0^{\infty} e^{-\lambda x} dx\\&=\int_0^{\infty} \frac{x}{e^{\lambda x}(e^x-1)}dx+\frac{1}{2(\lambda+1)^2}-\frac{1}{\lambda}\end{align*}$$

Recall the Hurwitz zeta function:

$$\zeta (s,w)=\frac{1}{\Gamma (s)}\int_0^{\infty}\frac{t^{s-1}}{e^{wt}(1-e^{-t})}dt$$



Now integrate back twice:

$$\int f''(\lambda)d\lambda =\frac{d}{d\lambda}\ln\Gamma (\lambda+1)-\frac{1}{2(\lambda+1)}-\ln \lambda+\mathcal{C}$$

Letting $\lambda\to\infty$ reveals that $\mathcal{C}=0$

$$\int f'(\lambda)d\lambda =\ln\Gamma (\lambda+1)+\lambda (1-\ln\lambda)-\frac{1}{2}\ln (\lambda +1)+\mathcal{C'}$$

Taking $\lambda\to\infty$ we have $\mathcal{C'}=\ln\sqrt{\dfrac{1}{2\pi}}$ (easily deduced using Stirling's approximation)

Now letting $\lambda\to 0$ gives us the result:

$$\int_0^{\infty} \frac{1}{x}\left(\frac{1}{e^x-1}+\frac{1}{2e^x}-\frac{1}{x}\right)dx=\ln\sqrt{\dfrac{1}{2\pi}}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.